PENGARUH ENTREPRENEURIAL MARKETING TERHADAP KINERJA PEMASARAN DENGAN VARIABEL MODERASI BIMTEK DAN BANTUAN PERALATAN - Liswati Liswati; Baiq Handayani Rinuastuti; Lalu Edy Herman Mulyono (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2020)
This study aims to investigate the effect of Entrepreneurial Marketing on Marketing Performance with the Moderating Variable of Technical Guidance and Equipment Assistance. To achieve this goal a quantitative approach was used with a population of UMKM owners / managers in the city of Mataram with a total sample of 120 respondents. Data analysis uses structural equation modeling (SEM analysis) Moderated Regression Analysis (MRA) with smartPLS applications. The results showed that Entrepreneurial Marketing had a positive and significant effect on the Marketing Performance of UMKM in the City of Mataram. For the moderating effect of Equipment Assistance, there is the role of Quasi Moderation in the influence of Entrepreneurial Marketing on Marketing Performance, while for Technical Guidance there is the role of Moderation Homologist in the influence of Entrepreneurial Marketing on Marketing Performance of UMKM in Mataram City.Penelitian ini bertujuan untuk melakukan investigasi pengaruh Entrepreneurial Marketing terhadap Kinerja Pemasaran dengan Variabel Moderasi Bimbingan Teknis dan Bantuan Peralatan. Untuk mencapai tujuan ini digunakan pendekatan kuantitatif dengan populasi pemilik / manager UMKM di Kota Mataram dengan jumlah sampel sebanyak 120 responden. Analisis data menggunakan model persamaan struktural (analisis SEM) Moderated Regression Analysis (MRA) dengan aplikasi smartPLS. Hasil penelitian menunjukkan bahwa Entrepreneurial Marketing berpengaruh positif dan signifikan terhadap Kinerja Pemasaran para pelaku UMKM di Kota Mataram. Untuk pengaruh moderasi Bantuan Peralatan, terdapat peran Quasi Moderasi dalam pengaruh Entrepreneurial Marketing terhadap Kinerja Pemasaran, sedangkan untuk Bimbingan Teknis terdapat peran Homologiser Moderasi dalam pengaruh Entrepreneurial Marketing terhadap Kinerja Pemasaran para pelaku UMKM di Kota Mataram.